THE EFFECT OF GOVERNMENT CONSUMPTION AND GOVERNMENT INVESTMENT AS INTERVENING VARIABLES TO GROWTH IN INDONESIA - Suparjito, Suparjito; Sarungu, Julianus Johnny; Soesilo, Albertus Magnus; Samudro, Bhimo Rizky; Hasanah, Erni Ummi (Muhammadiyah University Press, 2019)
Fiscal policy and monetary policy are the two macroeconomic policies used by the government and monetary authorities in order to create a stable economy. The budget deficit policy is one form of fiscal policy implemented by the government in order to realize a high level of economic growth, a controlled inflation rate and open up new job opportunities to reduce unemployment. The impact of the implementation of the budget deficit policy on the level of economic growth is a long debate. Neoclassical groups argue that the implementation of budget deficit policies is detrimental to the economy, as it lowers the rate of economic growth. Keynesian groups argue that the implementation of the budget deficit policy is very good for the economy, because it triggers the rate of economic growth by increasing the number of demand for goods and services through increased government spending. While the Richardian people argue that the implementation of budget deficit policy has no effect on the economy. The data used in this study is data from 1981-2014 which consists of budget deficit, government consumption, government investment and economic growth rate. The method of analysis in this research is using Partial Least Square-Path Modeling (PLS-PM) approach with SMART-PLS analysis tool which aims to analyze the direct and indirect influence of the implementation of budget deficit policy toward the level of economic growth through government consumption and government investment. The results show that the implementation of the budget deficit policy can increase economic growth through increased government investment spending. Keywords: budget deficits, government investment, government consumption, growth.